The Indonesian Development Experience : A Collection of Writings and Speeches - Nitisastro, Widjojo (Book collections on Project MUSE., 2011)
This book is a rich selection of speeches and writings of Professor Widjojo Nitisastro of the University of Indonesia, who has radically changed the command economy under Soekarno into development planning using economic analysis under Soeharto. He is one of the most respected and influential economists of the twentieth century. He is also the first Indonesian demographer. This background has contributed to his wide focus on development issues such as poverty, food security, education, health, and family planning. This book provides invaluable insight for all who are interested in Indonesia's.